Religion as Moral Infrastructure: Lived Islam, Welfare Governance, and the Family Hope Program in Indonesia - Muhammad Alim Ihsan; Sakaruddin Mandjarreki; Suparman Suparman (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This article examines how Islam, lived as everyday practice, operates as a moral infrastructure shaping welfare meanings, ethical compliance, and state–society relations in the implementation of Indonesia’s Family Hope Program (Program Keluarga Harapan, PKH) in Palu City, Central Sulawesi. The study aims to address the limitations of dominant administrative and economistic approaches to welfare policy by demonstrating why religion must be taken seriously as an operative moral force within public policy practice, particularly in Global South contexts. Employing a qualitative descriptive–interpretive design, the research draws on field observations, in-depth interviews with PKH beneficiaries, program facilitators, local officials, and religious leaders, as well as analysis of policy documents and program guidelines. Data were analyzed thematically through iterative processes of data reduction, categorization, and interpretation to capture the lived religious meanings embedded in welfare practices. The findings reveal three key patterns. First, beneficiaries conceptualize welfare not as material accumulation or class mobility, but as a condition of sufficiency, calmness, and security, sustained primarily through children’s education, food provision, and basic healthcare. Second, PKH assistance is understood as a religious amanah (trust), generating compliance and disciplined assistance management through internalized moral emotions such as gratitude, fear of sin, shame, and parental responsibility rather than fear of administrative sanctions. Third, PKH functions as an arena of moral governance in which state regulations gain effectiveness by resonating with local Islamic moral idioms, mediated by program facilitators, local authorities, and kiai. The study has important implications for welfare policy and religious studies. It demonstrates that welfare governance in the Global South cannot be adequately understood through secular or technocratic lenses alone, as policy effectiveness depends on its capacity to engage existing religious moral ecologies. The originality of this research lies in its contribution to reframing welfare policy as a site of lived religion and moral governance.